1906
DOI: 10.1002/cber.19060390124
|View full text |Cite
|
Sign up to set email alerts
|

α‐ und β‐Kieselsäure in Lösung

Abstract: 116 gelingt es, allen Monoathylather zu entfernen. Aus dem Benzol krystallisirt dann der Dimethylather rein aus. Aus der Lauge wird der reine Monoather gefallt. Der neben dem Aethylrnethyllther entstehende Monomethylather hat den Schmp. 232-23 "). [Mittheilung aus der Physik.-Techn. Reichsanstalt.] (Eingegangen am 22. December 1905; vorgetragen in der Sitzung vom 9. December von Hrn. F.Mg1ius.) Mehr und inehr bricht sich die Erkenntniss Bahn, dass unsere chernischen Symbole fiir die S i i u r e n ungesgttigte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1910
1910
1953
1953

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 9 publications
0
8
1
Order By: Relevance
“…Specific values so reported are 1704, 1751 and 1780 cal./20 g. at temperatures of 4.40, 17.56 and 19.54°. From data of TableIvalues at these same temperatures are 1342, 1575 and 1608 cah/20 g. These values are somewhat lower than those of Fredenhagen because of one or both of the following possibilities:(1) values from the present work, below 23°, are dependent on extrapolation of vapor volumes;(2)…”
contrasting
confidence: 45%
“…Specific values so reported are 1704, 1751 and 1780 cal./20 g. at temperatures of 4.40, 17.56 and 19.54°. From data of TableIvalues at these same temperatures are 1342, 1575 and 1608 cah/20 g. These values are somewhat lower than those of Fredenhagen because of one or both of the following possibilities:(1) values from the present work, below 23°, are dependent on extrapolation of vapor volumes;(2)…”
contrasting
confidence: 45%
“…The present theory for the setting of these gels of silicic acid is derived from the statement of Mylius and Groschuff (7) and others, that in the instantaneous reaction of the acid with the sodium silicate, a simple silicic acid is formed. This is probably a monosilicic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The ease with which the silicic acid first formed passes through a dialyzer membrane has been mentioned, also the fact that this ability is soon lost. The albumin test of Mylius and Groschuff (59), showing low molecular weight in freshly formed sols of silicic acid, has been cited. They found that the sol, upon standing, changed from the simple a-silicic acid to the very complex ß-silicic acid.…”
Section: B the Cellular Theorymentioning
confidence: 99%